Correctable Cause of Dilated Cardiomyopathy in an Infant with Heart Failure: ALCAPA Syndrome - Osman Güvenç; Murat Saygı; Erkut Öztürk; Alper Güzeltaş (Güncel Pediatri)
Anomalous origin of the left coronary artery arising from pulmonary artery ALCAPA syndrome is a rare congenital heart disease seen in children. If untreated, it may lead to congestive heart failure, dilated cardiomyopathy (DCM), ischemic and arrhythmic complications may lead to patient’s death. ALCAPA is diagnosed with echocardiography; in the patients of suspected diagnosis, computerized tomography, magnetic resonance imaging and cardiac catheterization are used for further testing. Surgically correctable ALCAPA syndrome must be considered as etiology of DCM in children. In this report, we presented the case of an infant that was referred to our center with the diagnosis of DCM, who was echocardiographically diagnosed with ALCAPA syndrome and successfully treated with surgery, as well as a review of recent literature.